2013
DOI: 10.1557/jmr.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

Interface-driven microstructure development and ultra high strength of bulk nanostructured Cu-Nb multilayers fabricated by severe plastic deformation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
122
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 41 publications
3
122
0
Order By: Relevance
“…Most remarkably, the material self organizes to a narrow set of predominant interfaces near {4 4 11}o11 11 84Cu (D)||{112}o1104Nb, and including some fraction of {112}o1114Cu(C)||{112}o1104Nb interfaces. A rationale for its development was recently proposed 34 . When h refines to 50 nm, the amount of the {112}o1114Cu (C)||{112}o1104Nb interface increases and twins form in the Cu layers 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…Most remarkably, the material self organizes to a narrow set of predominant interfaces near {4 4 11}o11 11 84Cu (D)||{112}o1104Nb, and including some fraction of {112}o1114Cu(C)||{112}o1104Nb interfaces. A rationale for its development was recently proposed 34 . When h refines to 50 nm, the amount of the {112}o1114Cu (C)||{112}o1104Nb interface increases and twins form in the Cu layers 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…This result is in agreement with the trends observed in recent room temperature studies on Cu-Nb NMMs. 5 Second, the room temperature hardness saturates and the high temperature hardness decreases at L = 7 nm for the ARB Cu-Nb NMM. By contrast, the strength continues to increase with decreasing layer thickness for all temperatures in the PVD Cu-Nb NMM, even for the smallest layer thickness of L = 5 nm.…”
mentioning
confidence: 93%
“…Experiments have shown that these interface-rich composites are several times stronger and structurally more stable after exposure to high-temperature and/or radiation environments than their constituents. [4][5][6][7][8][9] The high temperature strength of the NMMs, however, has not been quantified. Current strategies for understanding the influence of temperature on NMM performance typically involve room temperature tests on NMMs that have been previously exposed to elevated temperatures.…”
mentioning
confidence: 99%
“…[54,55] Compared with other texture measurement techniques, NeD enables statistically relevant data without potential modifications due to surface preparation. Texture measurements also provide a robust indicator of the primary deformation mechanisms, such as when interface-driven plasticity, [28,56] grain boundarymediated processes, [57] deformation twinning, [58][59][60] and partial-mediated slip [61] prevail. Figure 3 shows examples of textures at the micron scale and nanoscale in the form of pole figures, a compact way to present texture, as well as the standard texture presentation for Zr (albeit not for Nb).…”
mentioning
confidence: 99%
“…This is in remarkable contrast to cubic-based nanolayered systems produced by the same technique.Thus, critical length scales below which sizedependent or interface-driven mechanisms emerge in the hcp-bcc system, should they exist, must lie below 90 nm.Furthermore, based on the exceptional properties discovered for ARB Cu-Nb systems, [9,56,[71][72][73][74] we envision that the Zr-Nb nanolayered material will exhibit many unusual and interesting properties, potentially far exceeding those of current coarse-grained Zr.This study opens up an innovative route to manufacturing hcp and bcc nanostructured metals as well as a novel material for pioneering hcp/bcc interface and nanoscale hcp research.…”
mentioning
confidence: 99%